Epidemiology of Important Poultry Diseases in Nepal - Gompo, T. R.; Pokhrel, U.; Shah, B. R.; Bhatta, D. D. (Nepalese Veterinary Journal, 2019)
Despite the rapidly growing poultry industry throughout Nepal, the periodic outbreaks of diseases and infections in poultry birds led to huge production loss. The aim of this study was to identify the top ten poultry diseases in Nepal and an analysis of their seasonal distributions. A cross-sectional study was performed to describe the distributions of major poultry diseases diagnosed from April 2018 to April 2019 at Central Veterinary Laboratory, Nepal. Out of 2358 observations recorded at the CVL registry at that period, only 2271 observations qualified for the final analysis. Among 2271, removing the missing values, only 1915 observations were used to describe bird characteristics such as median age and mean flock sizes. Descriptive analysis and graphical representation was performed in R studio (Version 1.0.143) and MS excel 2010 respectively. The top ten diseases identified with highest to lowest incidence were: colibacillosis 26% (584/2271), mycotoxicosis 13% (301/2271), ascites 10% (232/2271), complicated chronic respiratory disease (cCRD) 9% (196/2271), infectious bursal disease (IBD) 7% (155/2271), Newcastle disease (ND) 7% (148/2271), avian influenza (AI) 3% (76/2271), salmonellosis 2% (40/2271), infectious bronchitis 1% (33/2271), coccidiosis 1% (25/2271) and non-specific diseases accounts for 21% (481/2271). Cases of colibacillosis were predominant all year round. Mycotoxicosis was seen mostly during pre-monsoon and monsoon season. Ascites and IBD were common during spring and winter seasons. cCRD was most common during summer and winter months. AI kept changing the disease outbreak pattern but it was most common during spring and summer. The number of cases of Salmonella, IB and coccidiosis were not sufficient to provide the seasonal trend. Identification of common poultry disease and their seasonal distributions is useful in taking preventive measures such as vaccination and good management practices to minimize their incidence in the future.